PENERAPAN KURIKULUM 2013 PADA MATA PELAJARAN AL QUR’AN HADITS DI MTs RAUDLATUL ULUM KARANGPLOSO - Mohammad Wibawadi; Chalimatus Sa’dijah; azhar haq (VICRATINA, 2019)
The research in this paper based on background of phenomenon the implementation of learning in schools that are not yet in accordance with the provisions curriculum of 2013. There is many schools use it curriculum of 2013 but many still use it Educational Unit Level Curriculum . The aplication currriculum of 2013  is still complicated in planning, implementation, and assessment making implementation in schools not optimal. Islamic religious education subjects have already applied the curriculum of 2013 yet are still not maximal in applying it one of them is subject of the Qur’an Hadits. There are several focuses in writing and research in this theses, are : 1) How curriculum of 2013 planning on the subjects of the Qur’an Hadits at MTs Raudlatul Ulum Karangploso. 2) How curriculum of 2013 implementation on the subjects of the Qur’an Hadits at MTs Raudlatul Ulum Karangploso. How curriculum of 2013 assessment on the subjects of Qur’an Hadits at MTs Raudlatul Ulum Karangploso.